Toxic water, toxic system: environmental racism and Michigan's water war - Mascarenhas, Michael (University of California Press, 2024)
"This book makes explicit the racial, ethnic, and gendered forms of environmental injustice that culminate from the collective, intersecting, and multi-scaler consequences of a seemingly anonymous authoritarian state willing to maintain white supremacy at any cost, including poisoning an entire city and shutting off water to thousands of people"--